South African Sucrose Quality in Sugar: Determinants and its Empirical Implications - Doorasamy, Mishelle; Rhodes, Bruce (Journal of Economics and Behavioral Studies, 2017)
The study investigates which factors determine sucrose quality in the South African sugar cane production process. Though South Africa is the 8th largest producer of sugar cane in the world and the highest in Africa, a decline has been observed in the production of high quality sugar in the country. The study adopts the Auto Regressive Distributive Lags (ARDL) technique to analyze sugar cane production time series data from 1980 to 2016 in South Africa. Ten variables were tested, including Average Temperature, Stalk growth, Evaporation, and Soil Water Content (100mm). Our findings revealed that on both the short and long run, some of the variables investigated have the tendency of increasing sucrose level in sugar cane while an increase in other variables would decrease sucrose level altogether. However, the impact of Soil Water Content (100mm) appears not to be statistically significant on sucrose production in our regression model in the short and long run. Of special interest are Stalk growth (Reference sugar cane) and average temperature, as their values are more significantly germane as regards the quantity of sucrose obtained during sugar cane processing in South Africa.